Comparison of Packed Cell Volume Changes after Erythropoietin Administration and Blood Transfusion in Patients with Anemia of Chronic Kidney Disease on Hemodialysis - Bajracharya, Anju; Bajracharya, Jayendra (Nepal Journal of Health Sciences, 2021)
Introduction: Anemia of chronic kidney disease (CKD) can be managed by regular administration of erythropoiesis stimulating agents (ESAs) and/or blood transfusion. The response to these therapies can be monitored by serial packed cell volume (PCV).Objective: This study was done to compare the temporal changes in PCV after ESA therapy and blood transfusion in patients with recently diagnosed anemia in CKD stage 5 on hemodialysis (CKD 5 HD).Methods: Medical records of patients undergoing hemodialysis at the National Kidney Center, Balaju, Kathmandu from July to September 2013 were examined retrospectively. The data collected were analyzed using Minitab 16.Results: A total of 44 patients were on ESA therapy while 48 patients were on blood transfusion. The mean PCV at the start of blood transfusion was significantly lower than the mean PCV at the start of ESA therapy (p = 0.000) but at four weeks, the mean PCV in blood transfusion group was significantly greater than that in ESA therapy group (p = 0.008). At eight weeks and twelve weeks, the mean PCVs in both groups were not significantly different from each other (p = 0.949 and p = 0.747).Conclusions: Blood transfusion increases PCV immediately and in sustained manner while with ESA therapy, the response takes a longer time to manifest. A large number of non-responders to ESA therapy may have influenced the findings of this study. It is recommended that adequate dosing of ESA and attention to comorbid conditions be followed during ESA therapy.Keywords: Anemia; chronic renal insufficiency; blood transfusion; hematinics.